Prevalence and factors associated with probable sarcopenia in southern Brazil: a population-based study - Cristina Paludo; Tatiane Gonzalez; Pedro Soares; Rodrigo Meucci (James Cook University, 2024)
Introduction: There are few studies on probable sarcopenia in rural areas. This study aims to assess prevalence of probable sarcopenia and its associated factors in older adults living in the rural area of a municipality in southern Brazil. Methods: This cross-sectional study assessed data from the second wave of the EpiRural Cohort Study. Structured questionnaires, handgrip strength, gait speed, and anthropometric measurements were collected from 651 older adults. The criteria from the European Working Group on Sarcopenia in Older People 2 were used in this study. Chi-square test and logistic regression with robust variance were performed. Results: Prevalence of probable sarcopenia was 19.2% (95% confidence interval (CI): 16.3-25.2%). Male sex (prevalence ratio (PR) 1.61; 95%CI 1.17-2.21), age ≥80 years (PR 4.15; 95%CI 2.65-6.50), underweight (PR 1.90; 95%CI 1.23-2.93), diabetes mellitus (PR 1.80; 95%CI 1.20-2.73), and hospitalization in the past year (PR 2.00; 95%CI 1.36-2.91) were significantly associated with probable sarcopenia. Conclusion: One in five rural older adults have probable sarcopenia. Older adults living in rural areas need frequent measurements of muscle strength, and greater investments should be made to minimize the physical disability caused by sarcopenia among this population.